1981
DOI: 10.1161/01.str.12.5.627
|View full text |Cite
|
Sign up to set email alerts
|

Transient ischemic attacks and external carotid artery. A retrospective study of 23 patients with an occlusion of the internal carotid artery.

Abstract: 627allowed demonstration of marked microcirculatory changes occuring during vasospasm which cannot be detected by macroscopic techniques. SUMMARY Twenty-three patients with occlusion of an internal carotid artery hare been followed 5 to 60 months after angiography. None had a later permanent stroke. Eight had delayed TIAs in the occluded internal carotid area, never in another area. In these TIAs the role of the homolateral external carotid artery is emphasized, because in the 8 cases this artery was the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…These results compare favourably with the collected studies analysed by Cole et al 12 In that survey only the retrospective study of Bogousslavsky et al 4 showed no deaths or strokes in a mean 27 month follow up period. Eight of their patients had delayed TIAs, and each of these had disease of the ipsilateral external or common carotid arteries, or an abnormality of the internal carotid artery stump.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These results compare favourably with the collected studies analysed by Cole et al 12 In that survey only the retrospective study of Bogousslavsky et al 4 showed no deaths or strokes in a mean 27 month follow up period. Eight of their patients had delayed TIAs, and each of these had disease of the ipsilateral external or common carotid arteries, or an abnormality of the internal carotid artery stump.…”
Section: Discussionsupporting
confidence: 84%
“…12 The number of patients with significant strokes and residual symptoms after the occlusion of an internal carotid artery are less impressive than initially suspected, with only 27% having severe complicated strokes and 73% being asymptomatic or experiencing only transient or mild focal neurological disorders. 3 Occlusion of the internal carotid artery may, however, be associated with transient or fixed neurological symptoms after the occurrence of the occlusion, and the evidence strongly suggests that such symptoms are frequently related to embolic disease originating from the external carotid artery 4 or the proximal blind stump of the internal carotid artery. 5 This concept is in direct conflict with the opinion of Gomensoro et al that "when a lesion progressed to complete thrombosis, there was no longer any possibility for emboli to pass into the distal circulation.…”
mentioning
confidence: 99%
“…Embolization from the stump through collateral pathways could also be considered in case 2. Such a mechanism has already been reported [13][14][15] and ECA collateral channels appear to have the same pathogenic role than in ECA atheromatous stenosis. In contrast to these cases, in case 3 head turning suggesting recurrent compression of VAs was responsible for transient aphasia.…”
Section: Discussionsupporting
confidence: 56%
“…19 -"- 20 The reasons for this is the lack of a reliable non-invasive method for their study and the risks associated with repetitive arteriography. Consequently, even if the vascular territories of subsequent cerebrovascular symptoms were noted, their pathogenesis remained unknown due to the lack of information about the actual distribution of obstructive lesions and their collateralization at the time the cerebrovascular event occurred.…”
Section: L3mentioning
confidence: 99%